The Effect of Feedback on the Application of Based Chemistry Practicum Modules on Local Content-Students' Science Process Skills - Sari, Ratih Permana; Hasibuan, Molani Paulina; Sulastri, Sulastri (Jurnal Pendidikan dan Pengajaran, 2021)
This study aims to analyze the effect of feedback from local content-based practicum modules on students' science process skills. Research subjects for product trials developed in this study were students of class XI using a purposive sampling technique with a sample size of 60 students. The method used in this research is quasi-experimental (quasi-experimental). The research instrument was a feedback rubric on applying a local content-based practicum module, observation sheets, and tests on the results of Science Process Skills (KPS). Data processing and analysis is carried out by comparing the initial and final science process skills scores by looking at the science process skills N-Gain score. Hypothesis testing uses the T-test to apply a local content-based practicum module on science process skills by analyzing the initial and final science process skills scores. The highest percentage result lies in the indicator of planning an experiment or investigation and using experimental tools and materials, namely 90%. There is a difference between a class that implements a local content-based practicum module and is given feedback with a class that uses a regular module for each class. The experimental class had an N-gain value of 0.75 or in the high category, while the control class had an N-gain value of 0.64 or in the moderate category. There are differences in students' Science Process Skills (KPS) using local content-based practicum modules with conventional practicum modules.